1991
DOI: 10.1007/bf01650680
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of nucleolar margination in diagnostic cytopathology

Abstract: The diagnostic value of nucleolar margination, defined as the percentage of nucleoli touching the nuclear membrane, was investigated in 359 cytological preparations of benign and malignant lesions of the thyroid, breast, prostate and central nervous system. Premalignant lesions of the uterine cervix and non-invasive papillary carcinomas of the bladder were also examined. It was observed that the percentages in benign lesions were, in general, lower than in the malignant and that the values increased progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Moreover, the presence of nucleolar margination in the irradiated cells is indicative of increased protein synthesis and nucleocytoplasmic exchange (Montironi et al . 1991a, b, c). This nucleolar segregation probably reflects DNA binding and inhibition of DNA‐dependant RNA synthesis (Reddy & Svoboda 1968; Zatsepina et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the presence of nucleolar margination in the irradiated cells is indicative of increased protein synthesis and nucleocytoplasmic exchange (Montironi et al . 1991a, b, c). This nucleolar segregation probably reflects DNA binding and inhibition of DNA‐dependant RNA synthesis (Reddy & Svoboda 1968; Zatsepina et al .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of chromatin margination and segregation in the irradiated cells is indicative of increased nuclear‐cytoplasmic exchange, rapid growth and increased metabolism (Montironi et al . 1991a, b, c; Love & Soriano 1971; Ghadially et al . 1985; Teodori et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, margination of nucleoli was also noticed in this group. Nucleolar margination is a sign of increased protein synthesis and is frequently seen in variety of cancer cells (78,84). The histological picture of animals treated once with AuNPs, suggests that both citrate-and chitosan-capped AuNPs produce noxious effects to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…20 A surprising finding was a significant difference between the eccentricity of both nuclei and nucleoli between adenomas and carcinomas, when all cells and nuclei from adenomas were compared with those of carcinomas. Even more surprising was the fact that the nucleoli of adenomas were more eccentric than those of carcinomas because Montironi et al 57 found that nucleolar margination characterizes follicular carcinomas. This discrepancy may be explained by differences in eccentricity measure (centroid position differences in our study vs. frequency of nucleoli touching the nuclear border in the Montironi study 57 ).…”
mentioning
confidence: 99%
“…Even more surprising was the fact that the nucleoli of adenomas were more eccentric than those of carcinomas because Montironi et al 57 found that nucleolar margination characterizes follicular carcinomas. This discrepancy may be explained by differences in eccentricity measure (centroid position differences in our study vs. frequency of nucleoli touching the nuclear border in the Montironi study 57 ). Alternatively, there may be intrinsic differences between follicular and Hürthle cell carcinomas in nucleolar eccentricity as a marker of malignancy.…”
mentioning
confidence: 99%